Media, Mobilization, And Impact: Understanding The ‘All Eyes On Rafah’ Campaign - Hidayat, Mansur; Amin, Mahmud Muzaki Nurul (Institut Agama Islam Negeri (IAIN) Kudus, 2024)
This article explores the transformative influence of social media in shaping global narratives and rallying support during humanitarian crises, focusing on the case of the ‘All Eyes on Rafah’ campaign. Sparked by Israeli strikes on Rafah refugee camps, this campaign leveraged striking visuals and celebrity endorsements to achieve widespread visibility. Through an analysis of viral social media content, the study identifies critical factors driving the campaign’s success, such as the emotional impact of imagery and the heightened credibility brought by influential public figures. The findings demonstrate that these elements not only shifted global perceptions but also inspired tangible actions, including financial contributions and advocacy efforts. While no single factor can fully account for the campaign’s effectiveness, the synergy between compelling visuals, celebrity advocacy, and rapid information sharing emerges as central to advancing humanitarian narratives. These insights contribute to the understanding of effective crisis communication strategies and offer new directions for examining the intersection of media, mobilization, and humanitarian outcomes.